Capacity Building for the University Volleyball Student Activity Unit through Lecturer–Student Collaborative Coaching - Susanto, Ratno; Neolaka, Erwin S.; Wijaya, I Nyoman Wahyu Esa (Help: Journal of Community Service, 2025)
This community service initiative aims to enhance the university’s Volleyball Student Activity Unit (UKM) through a collaborative coaching model involving sports lecturers and talented student athletes. The program was developed in response to the limited participation and low performance levels of collegiate sports particularly volleyball stemming from the scarcity of qualified coaches, structured training programs, and adequate practice facilities. The implementation adopts a participatory approach, beginning with an assessment of UKM needs, followed by training sessions on game strategies and tactics, improvement of fundamental physical and technical skills, and strengthening of UKM organisational management. Coaching activities are jointly conducted by sports lecturers and highly motivated students with strong volleyball capabilities. Evaluation is carried out through observations of technical skills, member engagement, and internal tournament results held after the coaching program. The findings indicate significant progress in student discipline, teamwork, and essential volleyball techniques such as serving, passing, smashing, and blocking. Additionally, UKM has experienced an increase in membership across faculties and the emergence of a more dynamic and sustainable organisational structure. Beyond improving student performance, this program contributes to shaping a replicable coaching model and reinforces a positive sports culture within the university. Overall, the development of the Volleyball UKM through the collaboration of sports lecturers and talented students has successfully fostered a competitive, productive, and sustainability-oriented sports ecosystem.